Study and application of photo-modified cassava starch with lactic acid and UV-C irradiation - Santos, Thaís Paes Rodrigues dos [UNESP] (2021)
Sour cassava starch (SCS) is naturally modified through the joint action of anaerobic fermentation and sun-drying, but there appears be an immense variety in the quality of commercial SCS. The present study aimed to produce cassava starch with high expansion property (PCMS). After the establishment of the production conditions, PCMS was compared to commercial starches in terms of specific volume, carbonyl and carboxyl content, thermal and paste properties, as well as, about its use for the production of cheese bread. In order to obtain PCMS, a 5 × 5 factorial design was set to determine lactic acid concentrations and exposure times to UV-C irradiation. The optimal conditions for photo-modification were 20 g/kg of lactic acid concentration and exposure time at UV-C for 75 min. The specific volume of PCMS was 2.85 times higher than native cassava starch but did not differ from the starch with high expansion property. Compared to native cassava starch, the PCMS showed lower peak and setback viscosity, higher amylose content and alteration of gelatinization enthalpy. The cheese bread prepared with PCMS did not differ from those produced with the other two SCS; consequently, PCMS preserved and ensured product quality that may be destined for food industry.